New-graduate physiotherapists' training needs and readiness for telehealth. (18th November 2022) - Martin, Romany; Mandrusiak, Allison; Russell, Trevor; Forbes, Roma
ABSTRACT: Introduction: The COVID-19 pandemic has necessitated a rapid transition to telehealth for the delivery of many Australian physiotherapy services. Little is known about new-graduate training needs in this method of service delivery. Aim To explore the readiness and specific training needs of new-graduate physiotherapists for telehealth service delivery in Australia. Methods: Qualitative individual telephone interviews of new-graduate physiotherapists (n = 16) and two videoconference focus groups of supervisors of new-graduate physiotherapists (n = 7) were undertaken. Thematic analysis was used. Results: Two global themes each with three organizing themes were generated. The two global themes were "support needs for novice practitioners" and "how to best prepare for telehealth." Discussion and Conclusion: New-graduate physiotherapists and supervisors perceive that pre-professional exposure to, and practical skills training for, telehealth is essential. Elements such as undertaking physical assessments via telehealth, verbal communication, and effective clinical reasoning in telehealth assessment and treatment were highlighted as areas of need. Both stakeholder groups perceived that the rapid transition to telehealth challenged the self-efficacy of new-graduates as they did not have clinical experience to rely on. The preparation, and ongoing support of new-graduates to adopt telehealth in the workplace is considered critical given the shift in Australian healthcare to online platforms.